2001
DOI: 10.1021/ja0166848
|View full text |Cite
|
Sign up to set email alerts
|

Lipid II:  Total Synthesis of the Bacterial Cell Wall Precursor and Utilization as a Substrate for Glycosyltransfer and Transpeptidation by Penicillin Binding Protein (PBP) 1b of Eschericia coli

Abstract: An essential feature in the life cycle of both gram positive and gram negative bacteria is the production of new cell wall. Also known as murein, the cell wall is a two-dimensional polymer, consisting of a linear, repeating N-acetylmuramic acid (MurNAc) and N-acetylglucosamine (GlcNAc) motif, cross-linked via peptides appended to MurNAc. The final steps in the maturation of murein are catalyzed by a single, bifunctional enzyme, known as a high MW, class A penicillin binding protein (PBP). PBPs catalyze polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 19 publications
3
129
0
Order By: Relevance
“…Furthermore, lipid II contains a 55-carbon polyprenyl chain that renders it insoluble in water and difficult to handle in enzyme assays. To enable the study of bacterial transglycosylases, we and others (10,20,21) have established synthetic routes to natural lipid II and analogues containing truncated polyprenyl chains (10). We previously reported that compound 10, which contains a 35-carbon lipid chain, is a better substrate than natural lipid II to use for monitoring PBP1b activity in vitro (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, lipid II contains a 55-carbon polyprenyl chain that renders it insoluble in water and difficult to handle in enzyme assays. To enable the study of bacterial transglycosylases, we and others (10,20,21) have established synthetic routes to natural lipid II and analogues containing truncated polyprenyl chains (10). We previously reported that compound 10, which contains a 35-carbon lipid chain, is a better substrate than natural lipid II to use for monitoring PBP1b activity in vitro (10).…”
Section: Resultsmentioning
confidence: 99%
“…A major impediment to studying these enzymes has been that adequate supplies of lipid II cannot be obtained from natural sources. The development of synthetic approaches to make lipid II and analogues has solved the substrate problem (10,20,21), making it possible to assay inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…So far, access to Lipid II and variants was limited to groups having considerable synthetic expertise (14,16,17). We reasoned that it should be possible to produce Lipid II if membrane preparations carrying sufficient MraY and MurG activity were provided with the appropriate UDP-activated amino sugars and undecaprenyl phosphate in the presence of a suitable detergent.…”
Section: Synthesis Of Lipid II Andmentioning
confidence: 99%
“…The cell walls of all bacteria contain a layer of peptidoglycan, a biopolymer of the alternating amino sugars N-acetylglucosamine (D-NAc-Glu, NAG) and N-acetylmuramic acid (NAc-Mur, NAM), which is modified with pentapeptides of the sequence L-alanyl--D-glutamyl-L-lysyl-D-alanyl-D-alanine (in the case of S. aureus) that is attached to the 3-hydroxy group of the NAc-Mur sugar (Schwartz et al 2001;Breukink and de Kruijff 2006;de Kruijff et al 2008). The cross linkage of the peptides by penicillin binding proteins (PBPs) to macromolecules confers a structural rigidity and mechanical strength that prevents the bacterial protoplast to burst under the osmotic internal pressure.…”
Section: Lessons Learned From Druggable Targets In Bacteriamentioning
confidence: 99%